The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1186/1747-597x-6-2
|View full text |Cite
|
Sign up to set email alerts
|

The "Clubs against Drugs" program in Stockholm, Sweden: two cross-sectional surveys examining drug use among staff at licensed premises

Abstract: BackgroundThe objective of this study is to examine self-reported drug use among staff at licensed premises, types of drugs used, attitudes towards drugs, and observed drug use among guests. Results are presented from two measurement points (in 2001 and 2007/08). This study was carried out within the framework of the "Clubs against Drugs" program, which is a community-based multi-component intervention targeting licensed premises in Stockholm, Sweden.MethodsTwo cross-sectional surveys were conducted, the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…Additionally, the overall population in Sweden is perceived to have more restrictive attitudes towards illicit drug use as compared to the U.S.. For instance, although staff at licensed premises in Stockholm report high levels of drug use, almost 70% agree with Swedish drug laws stating that it should be illegal to be drug-intoxicated [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the overall population in Sweden is perceived to have more restrictive attitudes towards illicit drug use as compared to the U.S.. For instance, although staff at licensed premises in Stockholm report high levels of drug use, almost 70% agree with Swedish drug laws stating that it should be illegal to be drug-intoxicated [12]. …”
Section: Introductionmentioning
confidence: 99%
“…municipality, trade unions). Because prevalence studies at project initiation revealed that not only guests but also staff at licensed premises had high rates of drug use [31,32], a central part of the intervention has been to reduce drug use both among staff and guests through policy work [18]. One component of the intervention was therefore to use a comprehensive drug policy approach that included written policies, training for managers, staff education, drug‐testing and rehabilitation [33,34].…”
Section: Methodsmentioning
confidence: 99%
“…During the course of this RBS programme, stakeholders expressed concern of the increased problems related to illicit club drug use, and attention was therefore expanded to include illicit club drugs. Initial prevalence studies conducted by our group reinforced this concern, as illicit club drug use was found to be high both among guests and staff [18]. As a result, a new illicit club drug community intervention programme, ‘Clubs against Drugs’, was initiated in 2002.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations